2021
DOI: 10.1002/jev2.12168
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐derived small extracellular vesicles suppress CD8+ T cell immune function by inhibiting SLC6A8‐mediated creatine import in NPM1‐mutated acute myeloid leukaemia

Abstract: Acute myeloid leukaemia (AML) carrying nucleophosmin (NPM1) mutations has been defined as a distinct entity of acute leukaemia. Despite remarkable improvements in diagnosis and treatment, the long‐term outcomes for this entity remain unsatisfactory. Emerging evidence suggests that leukaemia, similar to other malignant diseases, employs various mechanisms to evade killing by immune cells. However, the mechanism of immune escape in NPM1‐mutated AML remains unknown. In this study, both serum and leukemic cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
(87 reference statements)
0
18
0
Order By: Relevance
“…In line with our findings, Erkes et al [ 54 ] demonstrated that mutant BRAF and MEK inhibitor-induced pyroptosis promoted T cell proliferation and contributed to the antitumor effects in melanoma. Notably, our previous study showed that tumor-derived extracellular vesicles inhibited CD8+ T cell immune function by suppressing creatine import, thereby enhancing the immune escape of NPM1mut leukemia [ 55 ]. Given the potent antileukemia capabilities of CD8+ T cells, contemporary immunotherapies aim to restore weakened T cell function in AML patients using a variety of strategies [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Erkes et al [ 54 ] demonstrated that mutant BRAF and MEK inhibitor-induced pyroptosis promoted T cell proliferation and contributed to the antitumor effects in melanoma. Notably, our previous study showed that tumor-derived extracellular vesicles inhibited CD8+ T cell immune function by suppressing creatine import, thereby enhancing the immune escape of NPM1mut leukemia [ 55 ]. Given the potent antileukemia capabilities of CD8+ T cells, contemporary immunotherapies aim to restore weakened T cell function in AML patients using a variety of strategies [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter targets SLC6A8-mediated creatine import and promotes immunosuppressive activities of CD8 + T cells. These observations indicate that TEV-miR-19a-3p might be a promising therapeutic target for AML carrying NPM1 mutations [ 57 ].…”
Section: Evs and Tumor Immune Suppressionmentioning
confidence: 99%
“…There is growing evidence that selective processing of mRNAs, including selective splicing, 3' selective polyadenylation and mRNA stability/translational regulation, is a major mechanism that promotes protein diversification (140)(141)(142)(143). Selective splicing and polyadenylation in eukaryotic cells generate multiple mRNA types with different 3'UTR lengths from the same gene (144,145).…”
Section: Pabpc1 and Immunoglobulin Secretionmentioning
confidence: 99%
“…T cells play a central role in mediating and coordinating the immune response against cancer, and many strategies aim to harness the potential of t cells to recognize and kill cancer cells in a targeted manner ( 176 , 177 ). The study found that serum from AML patients with NPM1 mutations and leukemia cells in a co-culture system impaired the immune function of CD8+ T cells ( 142 ). Mechanistically, leukemic cells secrete miR-19a-3p into the tumor microenvironment via small extracellular vesicles (sEVs), which are controlled by the NPM1 mutant protein/CTCF/PABPC1 signaling axis.…”
Section: Pabpc1 In Cancer Developmentmentioning
confidence: 99%